KEBIJAKAN PELAYANAN TERINTEGRASI PADA DINAS KEPENDUDUKAN DAN CATATAN SIPIL KOTA PEKANBARU (STUDI KASUS TENTANG INOVASI PELAYANAN AKTA KELAHIRAN TAHUN 2022) - Lingga Elissa; Hasanuddin ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
This study aims to determine the innovation of birth certificate services at the Pekanbaru City Population and Civil Registry Service and the factors that influence it. The research was conducted using a qualitative descriptive method that aims to describe the phenomena that occur. The data collection techniques used in this study were interviews, observation, documentation and note-taking. Innovation indicators based on innovation attributes or innovation variables according to Roggers in Suwarno (2008: 17) include: Relative advantages, Compatibility, Complexity, Triability, and Observability. The results of this study indicate that in innovation in birth certificate services at the Pekanbaru City Population and Civil Registry Service, there are 4 types of innovation, namely service innovation, process innovation, system innovation and conceptual innovation. Where all of this has been carried out by the Pekanbaru City Disdukcapil in realizing innovation in birth certificate services to the community. Then regarding the quality of birth certificate service innovation at Disdukcapil Pekanbaru City, it can be seen from the indicators (1) Relative advantage, (2) Conformity, (3) Complexity, (4) Possibility of trying, (5) Ease of observation. Based on the research results, it is known that the quality of innovation in birth certificate services at Disdukcapil Pekanbaru City is quite good, although there are still some deficiencies or problems that are used as evaluation material so that they can be corrected in the future. The driving factors include: 1) Support and commitment of program implementers, 2) Community needs are increasingly complex, and 3) Build a positive image of the public towards the services provided by bureaucrats. While the Inhibiting Factors include: 1) Online system disturbances, 2) Daily quota limitations, and 3) Lack of outreach to the community. Keywords: Innovation, Service, Birth Certificate, Disdukcapil Pekanbaru City.